Práticas de cuidado antirracistas: um estudo qualitativo com terapeutas ocupacionais no campo da saúde mental - Santos, Jamile (2025)
Introduction: Racism in Brazil is the result of enslavement with the construction of a Eurocentric national identity and can be understood as a combination of prejudice and power, favoring or removing access based on color or race. Occupational Therapy is a profession that questions and brings together social insurgencies and has sought to resume this proposal of anti-racist care, more recently. Considering that the practice of the category is tacit, we need to question how much the effects of racism affect the mental health of the black population. Objectives: To understand how issues related to racism have been incorporated into the care practice of occupational therapists in the field of mental health; to identify challenges and facilitators to produce anti-racist practice and to map strategies used in this practice. Methodology: This is a qualitative, descriptive, participatory research in which nine occupational therapists participated. They worked at least for one year in the area of mental health in Brazil and considered their practice anti-racist. The professionals answered an online questionnaire to identify sociodemographic data and participated in a semi-structured online qualitative interview. The data were analyzed using thematic analysis. Results: The first theme refers to the identification and recognition of racism to produce deviant movements in the practice of care; the second, highlights the need for more diverse and plural academic and professional training from the perspective of racial literacy to produce an anti-racist practice; the third theme sheds light on enabling dialogues between anti-racist occupational therapists in mental health with their peers in the production of this care to carry out a listening process that considers observable aspects in the interaction of black people in the services they receive care; and the fourth theme highlighted statements that aim to produce anti-racist mental health practices, both in epistemology and in increasing the number of black people in care spaces as workers and in a community that facilitates these productions. Discussion: Anti-racist practice in the field of mental health is based on the premise of the existence of racism as an experience that organizes the socio-affective relationships of black people. By recognizing this, occupational therapists may adopt a deviant stance. Continuing education based on racial literacy promotes a change in practice, given that the current training process of the category is colonialist. In this sense, it may adopt a stance of opening self-reflective dialogues with the team, with the people being monitored and their families, producing effects in their listening and observations both about racial identity, as well as the experiences of racism that produce mental suffering, and the way in which the therapeutic relationship between reference professionals and black people occurs. Final considerations: This study allowed us to verify that for occupational therapists who are attentive and sensitive to the effects of racism in the practice of care, the premise is that the production of mental suffering in black people occurs from racism, whether or not it is an evident factor in the discourse of the person being monitored, and that professionals have used the tools of the theoretical framework of mental health, facilitating the adherence and implementation of anti-racist practices. Thus, the relevance of considering the effects of racism on the mental health of the black population is highlighted, emphasizing the need for further studies on the topic.